Facile Synthesis of Galactosamine‐Stabilized Gold Nanoparticles with Sensitive Cd2+ Sensing. Issue 34 (10th November 2015) - Fu, Shanshan; Zhang, Xiuli; Ren, Guojuan; Chai, Fang; Wang, Chungang
Abstract: Cadmium is one of the most toxic and dangerous heavy‐metal elements to human health and environmental safety. Therefore, it is very useful to develop simple, rapid, and sensitive methods for the detection of Cd 2+ ions in real samples. Here, we report the simple synthesis of galactosamine‐functionalized gold nanoparticles (Galn‐GNPs) at room temperature. The Galn‐GNPs can be used as a colorimetric probe for the detection of Cd 2+ ions through localized surface plasmon resonance. A linear response to the concentration of Cd 2+ ions was observed in the range 1 to 100 nM . The detection limit is as low as 3 nM, which is below the maximum recommended contamination level of the World Health Organization for cadmium in drinking water of 3 ppb (15 nM ). The specific interactions of Cd 2+ ions with Galn‐GNPs provided excellent selectivity for the detection of Cd 2+ ions over 15 other metal ions (Pb 2+, Mg 2+, Zn 2+, Ni 2+, Cu 2+, Co 2+, Ca 2+, Mn 2+, Cr 3+, Ba 2+, Cr 6+, Ag +, Fe 3+, Al 3+, and Hg 2+ ). The selectivity of this system toward Cd 2+ ions was remarkably fivefold higher than that for other metal ions. The aggregation‐based change in color from red to purple occurred in less than 20 s. This method is simple and fast and has also been successfully applied to the detection of Cd 2+ ions in lake‐water samples. Abstract : Galactosamine‐stabilized gold nanoparticles are used as a highly selective, sensitive, and rapid colorimetric nanosensor for the detection of Cd 2+ ions in water. A linear response to the concentration of Cd 2+ ions is observed in the range 1 to 100 nM .